Composting of Cornstalks Used as Filtering Materials for the Pretreatment of Anaerobically Digested Centrate. Issue 2 (3rd April 2019) - Du, Longlong; Zhang, Zhiye; Li, Guoxue; Sun, Qiaoping; Zhang, Bangxi
Abstract: This study investigated the performance of composting cornstalks after used as the filtering materials for the pretreatment of anaerobically digested manure centrate. Results show that cornstalks could effectively remove suspended solids and organic matter in digested centrate. Direct composting of the used cornstalks could be achieved. The composting temperature increased rapidly and maintained at the thermophilic phase for more than 10 days. During 28 days of composting, the used cornstalks could be mature as indicated by the matrix pH of 7.37, electrical conductivity of 1.13 mS/cm, and germination index of higher than 100%. During composting, the carbon/nitrogen ratio of the used cornstalks decreased from 16.81 to 13.62. Moreover, cellulose in the used cornstalks was degraded by approximately 35.4% during composting.